A case of prostatic adenocarcinoma with Paneth cell-like appearance - Nakamura, Yasuhiro; Fujishima, Fumiyoshi; Watanabe, Mika; Taniuchi, Shinji; Ishida, Kazuyuki; Ishidoya, Shigeto; Arai, Yoichi; Sasano, Hironobu (Polish Journal of Pathology, 2011)
Paneth cell-like appearance of prostatic carcinoma cells with eosinophilic cytoplasmic granules is rarely reported, and is known to be associated with neuroendocrine differentiation of carcinoma cells. We report a case of prostatic adenocarcinoma with Paneth cell-like appearance that was localized next to conventional adenocarcinoma, and demonstrate its neuroendocrine differentiation by using immunohistochemical analysis. Paneth cell-like appearance of prostatic carcinoma cells should be recognized and considered as a sign of neuroendocrine differentiation due to the possible association with resistance to hormone therapy.